2012
DOI: 10.1111/j.1365-2052.2012.02341.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait loci for resistance to gastrointestinal nematode infections in Creole goats

Abstract: This study aimed to identify regions of the genome affecting resistance to gastrointestinal nematodes in a Creole goat population naturally exposed to a mixed nematode infection (Haemonchus contortus, Trichostrongylus colubriformis and Oesophagostomum columbianum) by grazing on irrigated pasture. A genome-wide quantitative trait loci (QTL) scan was performed on 383 offspring from 12 half-sib families. A total of 101 microsatellite markers were genotyped. Traits analysed were faecal egg count (FEC), packed cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Quantitative trait loci for traits such as birth and weaning weight (Mohammad Abadi et al, 2009;Visser et al, 2013), hair fiber characteristics (Cano et al, 2007;Visser et al, 2011), growth (Mohammad Abadi et al, 2009), body conformation (Marrube et al, 2007), parasite resistance (Bolormaa et al, 2010;De La Chevrotière et al, 2012), milk traits (Roldán et al, 2008), and α S1 -casein (Sacchi et al, 2005;Hayes et al, 2006;Dagnachew et al, 2011) have been identified in goats using microsatellite markers. With the availability of the Illumina Caprine 50K BeadChip (Illumina Inc., San Diego, CA;Tosser-Klopp et al, 2012, 2014, it is now possible to perform genome-wide scans in goats Genome-wide association study of conformation and milk yield in mixed-breed dairy goats with much greater resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait loci for traits such as birth and weaning weight (Mohammad Abadi et al, 2009;Visser et al, 2013), hair fiber characteristics (Cano et al, 2007;Visser et al, 2011), growth (Mohammad Abadi et al, 2009), body conformation (Marrube et al, 2007), parasite resistance (Bolormaa et al, 2010;De La Chevrotière et al, 2012), milk traits (Roldán et al, 2008), and α S1 -casein (Sacchi et al, 2005;Hayes et al, 2006;Dagnachew et al, 2011) have been identified in goats using microsatellite markers. With the availability of the Illumina Caprine 50K BeadChip (Illumina Inc., San Diego, CA;Tosser-Klopp et al, 2012, 2014, it is now possible to perform genome-wide scans in goats Genome-wide association study of conformation and milk yield in mixed-breed dairy goats with much greater resolution.…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive evidence in the literature for a definitive role for IgE in the regulation of FEC in numerous breeds of sheep and goat . In all studies, parasite‐specific IgE antibodies were negatively correlated with FEC; of concern, however, is that variable genetic correlations with body weight were observed in both sheep (to T. circumcincta ;) and goats (to H. contortus ;). This is potentially due to the mast cell degranulation event affecting the robustness of the tight‐junctional complex at the mucosal surface, allowing protein deficiencies to develop;…”
Section: Phenotypic Markers Of Resistance To Gin Infectionmentioning
confidence: 94%
“…The action of IgE is through a classical type I hypersensitivity reaction that is mediated by mast cell proliferation/degranulation in the mucosa of the GIT following exposure of the mast cells to L3 antigen . There is extensive evidence in the literature for a definitive role for IgE in the regulation of FEC in numerous breeds of sheep and goat . In all studies, parasite‐specific IgE antibodies were negatively correlated with FEC; of concern, however, is that variable genetic correlations with body weight were observed in both sheep (to T. circumcincta ;) and goats (to H. contortus ;).…”
Section: Phenotypic Markers Of Resistance To Gin Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bibliographic search at NCBI Pubmed Database (http://www.ncbi.nlm.nih.gov/) revealed few publications where caprine QTL are described (a representative list can be found at Table 1). For instance, De la Chevrotière et al [2] identified 13 QTL for resistance to gastrointestinal nematode infections in Creole goats by analysing 101 microsatellites. Quantitative trait loci affecting mohair [3,4] and conformation traits [5] as well as preweaning growth [6] have also been reported in Angora goats.…”
Section: Introductionmentioning
confidence: 99%